The Effect Of Cross Listing On The Accounting Quality Of Firms Cross Listed In East African Markets - Emmah W. Ndirangu; Cyrus Iraya (European Scientific Journal, ESJ, 2016)
Cross listing has been identified as a determinant of accounting quality. Prior empirical studies have differed on the effect of cross listing on accounting quality in different jurisdictions. The study of accounting quality in East Africa has however not incorporated the possible effect of cross listing. This research study sought to establish the effect that cross listing may have on the accounting quality of firms cross listed in East African stock exchanges. The study looked at three accounting quality metrics of firms cross listed in East Africa, namely, earnings management, timely loss recognition and value relevance of accounting information. The earnings management model used was the Lang, Raedy and Yetman (2003) earnings smoothing model. Timely loss recognition was investigated using the Basu (1997) model while value relevance was tested using the Lang, Raedy and Yetman (2003) model. These metrics were tested for differences during a three year period prior to cross listing and a three year period after cross listing. Accounting quality metrics for a total of six cross listed East African companies were analyzed. This study shows that earnings management did not occur around the cross listing dates. The value relevance of information presented by the cross listed firms did not change significantly, meaning that the ability of the summary accounting measures to accurately reflect the underlying economic value of the firms studied still remained as before the cross listing. There was no significant effect in terms of timely loss recognition in light of bad news and no indication of better prudence in the reporting of good news. The study finds that cross listing does not have an effect on the quality of reporting of firms cross listed within the East African Securities Exchanges.